2018
DOI: 10.1159/000492091
|View full text |Cite|
|
Sign up to set email alerts
|

High Fat Diet Upregulates Fatty Acid Oxidation and Ketogenesis via Intervention of PPAR-γ

Abstract: Background/Aims: Systemic hyperlipidemia and intracellular lipid accumulation induced by chronic high fat diet (HFD) leads to enhanced fatty acid oxidation (FAO) and ketogenesis. The present study was aimed to determine whether activation of peroxisome proliferator-activated receptor-γ (PPAR-γ) by surplus free fatty acids (FA) in hyperlipidemic condition, has a positive feedback regulation over FAO and ketogenic enzymes controlling lipotoxicity and cardiac apoptosis. Methods: 8 weeks old C57BL/6 wild type (WT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 60 publications
8
65
0
Order By: Relevance
“…Further pathway analysis showed that the common pathways possibly regulated by C16:0 and C18:0 include cytokine-cytokine receptor intervention, prolactin signaling pathway, retinol metabolism, fatty acid degradation, peroxisome, steroid hormone biosynthesis, PPAR signaling pathway, and arachidonic acid metabolism. These pathways have been found to be mostly involved in glucose and lipid metabolism [35][36][37][38], in accordance with the common biological processes found between the LSF group and the HSD group. These results indicate that the similarity in biological functions and mechanisms between C16:0 and C18:0 are mainly in relation to glucose and lipid metabolism, in which they act as substrates in metabolism, and the chain length is probably a key factor in determining their effects.…”
Section: C18:0/c16:0 Ratio and Insulin Resistancesupporting
confidence: 77%
“…Further pathway analysis showed that the common pathways possibly regulated by C16:0 and C18:0 include cytokine-cytokine receptor intervention, prolactin signaling pathway, retinol metabolism, fatty acid degradation, peroxisome, steroid hormone biosynthesis, PPAR signaling pathway, and arachidonic acid metabolism. These pathways have been found to be mostly involved in glucose and lipid metabolism [35][36][37][38], in accordance with the common biological processes found between the LSF group and the HSD group. These results indicate that the similarity in biological functions and mechanisms between C16:0 and C18:0 are mainly in relation to glucose and lipid metabolism, in which they act as substrates in metabolism, and the chain length is probably a key factor in determining their effects.…”
Section: C18:0/c16:0 Ratio and Insulin Resistancesupporting
confidence: 77%
“…Here, we showed that a HFD caused an increase in the oxidative capacity (reflected by the SDH-OD) in muscles from young-adult but not old mice. The increase in skeletal muscle oxidative capacity with HFD has been previously reported in young-adult rodents (Eshima et al, 2017;Garcia-Roves et al, 2007;Hancock et al, 2008;Li et al, 2016b;Miller et al, 1984;Sikder et al, 2018;Thomas et al, 2014;Turner et al, 2007). Interestingly, it has been reported that the expression of enzymes in the citric acid cycle, β-oxidation and respiratory chain is comparable to that with standard diet after 2 weeks of HFD, but similarly elevated after 8 and 16 weeks of a HFD (Sadler et al, 2012).…”
Section: Oxidative Capacitymentioning
confidence: 56%
“…Prolonged ketosis is also associated with upregulation of NAD + [75,82,121,122]. Increased levels of NAD + explain the upregulation of the histone deacetylases sirtuin-1 (SIRT-1) and SIRT-3 seen in the brains and peripheral tissues of animals fed a KD, as SIRTs are NAD + -dependent enzymes [123][124][125].…”
Section: Consequences Of Ketogenesis and Ketolysis In The Cnsmentioning
confidence: 99%